AI Search Exposure And Behavioral Intentions: Toward A Conceptual Framework For SME Marketing In Indonesia - Ahmed H A Albawwab (Ann Publisher, 2026)
Background. The rapid proliferation of AI-mediated search tools has fundamentally transformed how consumers discover and evaluate products online. Aims. Despite growing evidence of AI's influence on digital consumer behavior, a significant conceptual gap persists regarding how AI search exposure shapes behavioral intentions—particularly purchase and recommendation intentions—among consumers encountering Small and Medium Enterprise (SME) products. Methods. This systematic literature review synthesizes 20 scholarly sources published between 2020 and 2026, including peer-reviewed journal articles, institutional reports, and working papers, retrieved from Scopus and Google Scholar databases, to examine the relationship between AI search exposure and consumer behavioral intentions in SME marketing contexts. Following PRISMA 2020 guidelines, this review identifies three key themes: (1) AI search as a novel consumer touchpoint that reshapes discovery and evaluation processes; (2) trust and perceived credibility as central mechanisms linking AI exposure to behavioral outcomes; and (3) the unique vulnerabilities and opportunities that AI-mediated search presents for SMEs operating in digital markets. Result. This paper proposes a conceptual framework positioning AI search exposure as an antecedent of purchase and recommendation intention, mediated by consumer trust and perceived AI credibility. Conclusion. Theoretical propositions are developed to guide future empirical research. Implication. Implications for SME marketing strategy in Indonesia are discussed, with particular attention to E-E-A-T optimization strategies.